How venture capital investors view radical strategic change in high technology new ventures. (19th January 2010) - Gimmon, Eli; Benjamin, Eyal; Katzenstein, Liora
Radical strategic change, a common event in high technology new ventures, presents a conflict between potential opportunity and the risk of departing from a planned and approved strategy. This study explores investors' perspectives regarding RSC in their portfolio companies, based on interviews of 13 private investors who are active venture capitalists or business angels. The study explores the investors' views based on three theories of VC-entrepreneur relationships: agency theory, stewardship theory and game theory. The findings indicate three approaches taken by investors: avoidance, expectation and passivity. Since the success of radical strategic change is critical to venture performance, it is suggested that investors adopt the expectation approach, which optimises the prisoner's dilemma inherent in the VC-entrepreneur relationship during such events. The findings of this exploratory study indicate the need for further research.